2019
DOI: 10.1021/acs.joc.9b02672
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3-Ring Fused Pyrroles via Cu-Catalyzed 5-exo-dig Annulation of Alkyne-Tethered Enaminones

Abstract: A copper-catalyzed annulation of alkyne-tethered enaminones for the synthesis of 2,3-ring fused pyrroles is reported. The 5-exo-dig cyclization/olefin migration reaction delivers the multisubstituted pyrroles in 59–99% yields with 16 examples. This strategy features easily available starting materials, mild reaction conditions, and a cheap ligand-free copper catalyst. The atom-economic transformation provides a simple access to a variety of synthetic useful pyrroles and their derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…By contrast, existing AD annulation is limited to a few simple N-heterocycles, requires a stoichiometric base for annulation, and is catalyzed using specially designed complexes, necessitating the development of base-free, efficient, and ligand-free catalytic systems for the synthesis of other heterocycles, containing oxygen and partially hydrogenated indole and an acridine system, because of their omnipresence in most therapeutic and natural products (Figure ). ,, …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, existing AD annulation is limited to a few simple N-heterocycles, requires a stoichiometric base for annulation, and is catalyzed using specially designed complexes, necessitating the development of base-free, efficient, and ligand-free catalytic systems for the synthesis of other heterocycles, containing oxygen and partially hydrogenated indole and an acridine system, because of their omnipresence in most therapeutic and natural products (Figure ). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu's group reported a copper-catalyzed 5-endodig cyclization of alkyne-tethered enaminones 209 for the synthesis of 2,3-ring fused pyrrole derivatives 210 in mild reaction conditions (Scheme 47). [69] In this reaction, the ketone functionality did not participate. As depicted in Scheme 46, the π-alkyne copper intermediate 211 generated through the coordination of the alkyne to Cu(I).…”
Section: Metal-catalyzed Cyclizations Of 4-acetylenic Ketones With Ammentioning
confidence: 94%
“…However, the reactions with Nalkyne-substituted 13b (R 1 = CH 2 C≡CH, R 2 = Me) and unsubstituted 13c (R 1 = H, R 2 = Me) enaminones under these conditions did not give the desired products. 26 Scheme 5 Synthesis of 4,5,6,7-tetrahydroindol-4-ones via Cu-catalyzed 5-exo-dig annulation of alkyne-tethered enaminones Beccalli, Broggini et al 27 described the ruthenium-catalyzed conversion of 4-alkenyl-substituted isoxazol-5-ones into 1H-pyrroles, including 4,5,6,7-tetrahydroindoles. The process proceeds under thermal conditions in the presence of a ruthenium(II) catalyst without use of additional additives.…”
Section: Review Synthesismentioning
confidence: 99%
“…It was shown that a number of alkynyl-substituted enones, namely the derivatives of 2-(but-2-yn-1-yl)-3-(arylamino)cyclohex-2-en-1-ones 13 undergo CuI-catalyzed annulation to form tetrahydroindol-4-ones 14 (Scheme 5). 26…”
Section: Intramolecular Reactions Leading To Tetrahydroindoles 21 Rin...mentioning
confidence: 99%